Occurrence of tick-borne haemoparasites in nyala (Tragelaphus angasii) in KwaZulu-Natal and Eastern Cape Province, South Africa - Oosthuizen, Marinda C. (University of Pretoria, 2013)
Dissertation (MSc (Veterinary Tropical Diseases))--University of Pretoria, 2009.